2022
DOI: 10.3390/su141912889
|View full text |Cite
|
Sign up to set email alerts
|

Career Adaptability as a Strategy to Improve Sustainable Employment: A Proactive Personality Perspective

Abstract: Reaching full employment and reducing the unemployment rate is one of the 17 sustainable development goals (SDGs) issued by the United Nations to face COVID-19 and the complex global economic situation. Although governments, society, and organizations have made efforts towards SDGs, how employees exert their subjective initiative and enhance their career adaptability is fundamental to solve the employment issue. How to enhance employees’ career adaptability to strengthen their psychological ability to face car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…The findings of the study also suggest that academic self-concept can be improved through a better understanding of the indicators of academic performance (Valero-Valenzuela et al, 2021). This can help students identify the Kumbhakar Community's weaknesses and take corrective measures to improve their learning outcomes (Zhao et al, 2022). This, in turn, can help students become more confident and motivated, leading to improved academic performance (Almulla & Al-Rahmi, 2023).…”
Section: Discussionmentioning
confidence: 85%
“…The findings of the study also suggest that academic self-concept can be improved through a better understanding of the indicators of academic performance (Valero-Valenzuela et al, 2021). This can help students identify the Kumbhakar Community's weaknesses and take corrective measures to improve their learning outcomes (Zhao et al, 2022). This, in turn, can help students become more confident and motivated, leading to improved academic performance (Almulla & Al-Rahmi, 2023).…”
Section: Discussionmentioning
confidence: 85%
“…Graduates who take charge of their career management also get greater support from their company. The findings indicated that proactive personality and career adaptability have a significant relationship (Ghimire et al, 2021;Wen et al, 2022;Zhao et al, 2022). In other words, individuals with higher proactive personality scores were likelier to display interest in and curiosity about their future careers | 59 and show more confidence and a sense of control in their career orientation.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Career adaptability is defined as, "a psychosocial construct that denotes an individual's resources for coping with current and anticipated tasks, transitions, traumas in their occupational roles" (Savickas and Porfeli, 2012, p. 662). Proactive individuals have the propensity to foresee changes, identify opportunities and influence the environment to seize opportunities or counter threats which is linked to career adaptability (Zhao et al, 2022). Innovative individuals are equipped with skills that help them create and identify new ideas and novel ways of problem-solving, coordinating and dealing with (Teng et al, 2019) and creativity is also deemed as a precursor of career adaptability (Khalid and Ahmed, 2021).…”
Section: Sequential Indirect Impact Of Aptp Of Ieo On Entrepreneurial...mentioning
confidence: 99%